(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The need to improve employment opportunities and self-reliant necessitated this study to ascertain entrepreneurs’ rating of technical competencies required of business education graduates for establishing small and medium scale enterprises in Anambra State. One research question guided the study and two null hypotheses were tested at 0.05 level of significance. Descriptive survey research design was employed. The population consisted 811 small and medium scale entrepreneurs in Anambra State. A total of 243 of these entrepreneurs were sampled using the proportionate stratified sampling technique. The instrument for data collection was a structured questionnaire titled “Technical Competencies for Establishing Small and Medium Scale Enterprises Questionnaire (TCESMSEQ)” with 10 items. The instrument was validated by three experts. The reliability coefficient was 0.79 and was obtained using Crombach alpha method. Out of a total of 243 copies of the questionnaire distributed, 232 copies were retrieved which represented 95 percent retrieval. The data collected were analyzed using mean and standard deviation in answering the research questions and to check the respondent responses to the mean. The z-test and ANOVA were used for testing the null hypotheses at 0.05 level of significance. The findings revealed that technical competencies were considered required of business education graduates for establishing small and medium scale enterprises. The findings also revealed that gender had no significant influence on SMEs operators’ consideration of the technical competencies required of business education graduates for establishing small and medium scale enterprises. Based on the findings of this study, it was concluded that SMEs entrepreneurs in Anambra State were of the opinion that Business Education graduates required technical, competencies for the establishment of small and medium scale enterprises. The study recommended among others that the administrators of business education programmes should partner with entrepreneurs to organize training programmes that will help equip business education students with the requisite technical competencies